Isotopes and analogs of hydrogen – from fundamental investigations to practical applications. (1st September 2013) - Macrae, Roderick
Hydrogen has a central role in the story of the universe itself, and also in the story of our efforts to understand it. This paper retells the story of the part played by hydrogen and its stable isotope deuterium in the primordial synthesis of the elements, then goes on to describe how the spectrum of atomic hydrogen led to insights into the laws governing matter at the most fundamental level, from the quantum mechanics of Schrödinger and Heisenberg, through quantum electrodynamics, to the most recent work investigating the underlying structure of the proton itself. atomic hydrogen is unique among the elements in that the concept of isotopy – atoms having the same nuclear charge but different masses – is stretched to its limit in the isotopes of hydrogen, ranging from the well-known isotopes deuterium and tritium to exotic species such as muonium, muonic helium, and positronium. These atoms, or atom-like objects, have much to tell us about fundamental aspects of the universe. in recent years the idea of utilizing hydrogen either as an energy source (through nuclear fusion) or as an energy storage medium (bound in hydrides or other materials) has attracted much attention as a possible avenue to a post-oil energy future. Some of the more interesting recent developments are described here. dedicated to the memory of Brian C. Webster (1939 – 2008).